The Portrayal of The Main Character's Self-Actualization in The Karate Kid (2010) - Disty Nurul Izzaty (Passage: Journal of English Language and Literature, 2023)
The study aims to analyze how the main character in The Karate Kid (2010) achieves self-actualization needs in an intercultural setting. Employing close-reading to analyze the text, the study uses Maslow’s (2013) hierarchy of needs and Rogers’ (1967) five characteristics of a fully functioning person as the theoretical frameworks. It also uses Bordwell, Thompson and Smith’s film form (2017) as a tool to analyze the cinematic aspects of the film. The current study finds that Dre Parker, the main character in the film, successfully achieves self-actualization after fulfilling the four preceding needs, which are physiological, safety and security, love and belongingness, and self-esteem. It is also found that he expresses self-actualization through the five characteristics of a fully functioning person: openness to experience, existential living, trust feelings, creativity, and fulfilled life. Furthermore, the study concludes that the main character’s young age and cultural background do not hinder him from reaching self-actualization. In fact, self-actualization contributes to unite disparate cultures to a certain extent.